Analisis Perbandingan Tingkat Kerusakan Jalan pada Perkerasan Lentur Jalan Pala Raya 27 Kota Tegal - Divasaputri, Nashwa Adelia; Hadi, Suprapto; Nugroho, Toriq Rizky; Suryana, Diar; Arizki, Ivania Syilfa (Riwayat: Educational Journal of History and Humanities, 2025)
Road infrastructure is a vital component supporting economic and social development, yet pavement deterioration remains a significant challenge requiring systematic and accurate evaluation methods. This research evaluates the pavement condition of Pala Raya 27 Road in Tegal City by comparing three assessment methods: Surface Distress Index (SDI), Pavement Condition Index (PCI), and Bina Marga method. The study was conducted on a 1,500-meter local road section divided into nine 100-meter segments. Data collection involved visual inspection and measurement of pavement distresses including cracking, potholes, and rutting. Research findings indicate that the SDI method yielded an average value of 35.8 (Good condition) with two segments classified as lightly damaged. The PCI method produced an average value of 71.9 (Very Good condition) with 66.7% of segments in very good to good condition and 22.2% in fair condition. The Bina Marga method resulted in an average Road Condition Value (RCV) of 0.76 (Very Good condition) with 77.8% of segments in excellent condition. Notably, all three methods consistently identified segments 0+500-0+700 as critical areas requiring maintenance priority, despite differences in severity classification. The SDI method demonstrated highest sensitivity to pothole distress, while PCI provided more balanced assessment considering both severity and density. The Bina Marga method offered moderate evaluation adapted to local Indonesian conditions. This comparative analysis validates the consistency of the three methods while revealing their distinct characteristics and provides valuable guidance for pavement management decision-making. The research recommends that local residential roads like Pala Raya 27 utilize the Bina Marga or SDI methods due to their practical and economical procedures, while arteries or collector roads benefit from the more comprehensive PCI method. Immediate maintenance is recommended for critical segments to prevent further deterioration